2021
DOI: 10.1002/cam4.4171
|View full text |Cite
|
Sign up to set email alerts
|

Three models that predict the efficacy of immunotherapy in Chinese patients with advanced non‐small cell lung cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…A retrospective cohort study (Ge et al 2020 ) reported that males, squamous histology, no brain or liver metastases, any age, not beyond ≥ the third treatment line, with PR to the previous ICI, and monotherapy as previous ICI can benefit more from ICI rechallenge compared with other treatment. For initial immunotherapy, patients with smoking exposure (Kim et al 2017 ; Zhao et al 2021 ), better ECOG PS (Zhao et al 2021 ), higher PD-L1 expression (Duchemann et al 2021 ), and absence of liver metastasis (Zhao et al 2021 ) benefited more from the treatment. Theoretically, previous treatment lines and response to initial immunotherapy can lead to various efficacy of ICI rechallenge.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study (Ge et al 2020 ) reported that males, squamous histology, no brain or liver metastases, any age, not beyond ≥ the third treatment line, with PR to the previous ICI, and monotherapy as previous ICI can benefit more from ICI rechallenge compared with other treatment. For initial immunotherapy, patients with smoking exposure (Kim et al 2017 ; Zhao et al 2021 ), better ECOG PS (Zhao et al 2021 ), higher PD-L1 expression (Duchemann et al 2021 ), and absence of liver metastasis (Zhao et al 2021 ) benefited more from the treatment. Theoretically, previous treatment lines and response to initial immunotherapy can lead to various efficacy of ICI rechallenge.…”
Section: Discussionmentioning
confidence: 99%
“…NLR and dNLR can be utilized as novel biomarkers to determine the inflammation/immunity ratio in a plethora of solid tumors, and elevated NLR value is associated with lymphocytopenia and neutrophilia 28 . It is noteworthy that lymphocytes not only exert key roles in recognizing and killing diverse tumors but also assist ICIs in showing antitumor functions 29 . The elevated LDH is indicative of hypoxia-induced increase in tumor necrosis and tumor glycolytic activity and LDH level is inversely correlated with the response to ICIs and probably triggers hyperprogressive disease 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LDH can accelerate resistance to systemic therapy through the facilitation of immune escape and immune suppression 36 . The correlation of high LDH levels with poor prognosis in patients treated with ICIs is possibly due to the accumulation of serum tumor-derived lactic acid, which makes the CD8 T cells unable to export lactate and thus causes metabolic disorders, and indeed, dysregulation of T-cell metabolism is perhaps another regime of tumor resistance to various ICIs 29 . The LIPI score, combining dNLR and LDH, shows promising utilization value as a prognostic biomarker in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the patient cohort that will benefit from immunotherapy remains a pressing problem to be addressed. Previous studies have explored the prediction of immunotherapy efficacy from multiple perspectives, such as drug-based score ( 12 ), lung immune prognostic index (LIPI) ( 13 ), smoking ( 14 ), liver metastasis ( 15 ), lactate dehydrogenase (LDH) ( 16 , 17 ), tumor mutational burden (TMB) expression ( 18 ), neutrophil-to-lymphocyte ratio (NLR) ( 19 , 20 ), modified lung immune predictive index (mLIPI) scores ( 21 ), and so on. Despite achieving some results, the existing literature does not completely solve the problem of predicting immunotherapy efficacy.…”
Section: Introductionmentioning
confidence: 99%